The effect of operative technique and tibial osteotomy ratio on post-surgical complications in dogs with medial patella luxation - Kitshoff, Adriaan (University of Pretoria, 2024)
Mini Dissertation (MMedVet (Small Animal Surgery))--University of Pretoria, 2023.